Manual drilling in Africa; let us go beyond advocacy - Edwin Adenya; Fred Donde (2013)
This paper presents suggestions for the advancement in the adoption of manual drilling approaches in Africa. The objective of this support is to contribute to enabling African countries attain the Millennium Development Goals with more emphasis on rural water supply. The outline of the discussion is a self interrogation of why, despite advocacy for manual drilling approaches, the rural water supply coverage trends remain unchanged. It further outlines a number of ways in which manual drilling could be mainstreamed in the current water sector programmes. Whilst borrowing so much from previous experiences in manual drilling, the paper suggests a blend of both new and adopted social marketing approaches to advance the manual drilling agenda.